Comparative Analysis of the Clinical Course of Acute Appendicitis in the Bukhara Region with Information in the Literature (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Based on the goal of our scientific work, the medical history of 66 patients was studied, who were admitted in January-December 2021 with a diagnosis of acute appendicitis to the emergency surgery department of the central hospital of Vobkent district of Bukhara region. The analysis of the results of the treatment of the examined patients showed that there were differences in the appearance of the first clinical symptoms, the nature of clinical symptoms and the transition of acute appendicitis to complicated forms when compared with the information in the literature.